Identification of Lice Stored in Alcohol Using MALDI-TOF MS. Issue 3 (21st December 2020) - Benyahia, Hanene; Ouarti, Basma; Diarra, Adama Zan; Boucheikhchoukh, Mehdi; Meguini, Mohamed Nadir; Behidji, Makhlouf; Benakhla, Ahmed; Parola, Philippe; Almeras, Lionel
Abstract: Lice pose major public and veterinary health problems with economic consequences. Their identification is essential and requires the development of an innovative strategy. MALDI-TOF MS has recently been proposed as a quick, inexpensive, and accurate tool for the identification of arthropods. Alcohol is one of the most frequently used storage methods and makes it possible to store samples for long periods at room temperature. Several recent studies have reported that alcohol alters protein profiles resulting from MS analysis. After preliminary studies on frozen lice, the purpose of this research was to evaluate the influence of alcohol preservation on the accuracy of lice identification by MALDI-TOF MS. To this end, lice stored in alcohol for variable periods were submitted for MS analysis and sample preparation protocols were optimized. The reproducibility and specificity of the MS spectra obtained on both these arthropod families allowed us to implement the reference MS spectra database (DB) with protein profiles of seven lice species stored in alcohol. Blind tests revealed a correct identification of 93.9% of Pediculus humanus corporis (Linnaeus, 1758) and 98.4% of the other lice species collected in the field. This study demonstrated that MALDI-TOF MS could be successfully used for the identification of lice stored in alcohol for different lengths of time. Graphical Abstract: